A molecular interaction–diffusion framework for predicting organic solar cell stability - Ghasemi, Masoud; Balar, Nrup; Peng, Zhengxing; Hu, Huawei; Qin, Yunpeng; Kim, Taesoo; Rech, Jeromy J.; Bidwell, Matthew; Mask, Walker; McCulloch, Iain; You, Wei; Amassian, Aram; et al. (Nature materials, 2021)
Rapid increase in the power conversion efficiency of organic solar cells (OSCs) has been achieved with the development of non-fullerene small-molecule acceptors (NF-SMAs). Although the morphological stability of these NF-SMA devices critically affects their intrinsic lifetime, their fundamental intermolecular interactions and how they govern property–function relations and morphological stability of OSCs remain elusive. Here, we discover that the diffusion of an NF-SMA into the donor polymer exhibits Arrhenius behaviour and that the activation energy E a scales linearly with the enthalpic interaction parameters χ H between the polymer and the NF-SMA. Consequently, the thermodynamically most unstable, hypo-miscible systems (high χ ) are the most kinetically stabilized. We relate the differences in E a to measured and selectively simulated molecular self-interaction properties of the constituent materials and develop quantitative property–function relations that link thermal and mechanical characteristics of the NF-SMA and polymer to predict relative diffusion properties and thus morphological stability. Studies on the morphology stability of polymer donor–small-molecule acceptor blends relevant to solar cell stability reveal relationships between their intermolecular interactions and the thermodynamic, kinetic, thermal and mechanical properties.